1981
DOI: 10.1515/znb-1981-0705
|View full text |Cite
|
Sign up to set email alerts
|

Frontorbitale und 1.2-Hydridwanderungen in Carbeniumionen/ Frontier Orbitals and 1,2-Hydrogen Shifts in Carbenium Ions

Abstract: AbstractFor various carbenium ions it is shown that the energy value and the degree of localization of the LUMO have a significant influence on the energy barriers of 1,2-hydrogen shifts. The structures of the transition states are in line with the Hammond-Postulate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Barrier-free rearrangements to 3 (via methyl shift) or 4 (via fluoride shift) prevail over hydrogen 1,2-shift to 1 (regardless of which conformation of 5 is chosen as the initial geometry).10 Previously reported semiempirical calculations for 4 -3 predict a 70 kJ mol"1 barrier (as well as surprisingly high barriers for exothermic hydrogen 1,2-shifts in other conformationally mobile, electron-deficient cations). 23 While that theoretical result is consistent with our ab initio calculations on ion 5, the computational results contradict a recent proposal that, in solution, species 19 (a formal equivalent of 5) rearranges exclusively to 1, as eq 13 portrays. 24 The EBFlow results for free ions are consistent with eq 13, but it turns out that there is more than one pathway to 1.…”
Section: Discussionsupporting
confidence: 83%
“…Barrier-free rearrangements to 3 (via methyl shift) or 4 (via fluoride shift) prevail over hydrogen 1,2-shift to 1 (regardless of which conformation of 5 is chosen as the initial geometry).10 Previously reported semiempirical calculations for 4 -3 predict a 70 kJ mol"1 barrier (as well as surprisingly high barriers for exothermic hydrogen 1,2-shifts in other conformationally mobile, electron-deficient cations). 23 While that theoretical result is consistent with our ab initio calculations on ion 5, the computational results contradict a recent proposal that, in solution, species 19 (a formal equivalent of 5) rearranges exclusively to 1, as eq 13 portrays. 24 The EBFlow results for free ions are consistent with eq 13, but it turns out that there is more than one pathway to 1.…”
Section: Discussionsupporting
confidence: 83%
“…One setback, the systematic underestimation of Hbridged structures, has been shown. 6 On the other hand, the relative stabilities of all the structures considered in our investigation is predicted nearly in the same way by both methods. Deviations occur mainly with regard to the relative stabilities of the different conformations (e.g., 8, 9, 17).…”
Section: Discussionsupporting
confidence: 61%
“…Another three-membered cyclic compound 6 may be formed from l(c) [reaction (6)]: (6) As the data in Table I1 show that 6 is rather high in energy and the process l(c) -6 is, in contrast to reaction (5), highly endothermic, 6 is not expected to be generated from 1, whereas 7 should be the only stable three-membered cyclic cation among the C~HSNO+ species discussed so far. A 1,2 H shift separates the substituted acylium ion 3 from structure 8:…”
Section: Precursorsmentioning
confidence: 99%
“…CH 3 CX 2 + . Previous studies of the haloethyl cations indicated that the halogen substituents in the α-position stabilize the carbenium ion. , , This suggests that the 1,1-dihaloethyl cations will be the most stable isomers of the difluoro- and dichloroethyl cations. Indeed, our calculations indicate that the CH 3 CX 2 + cations 1 and 2 (Figure ) are at the global minima on the C 2 H 3 X 2 + potential energy surfaces for both X = F and X = Cl.…”
Section: Resultsmentioning
confidence: 94%
“…To date the potential energy surfaces of the dihalogenated ethyl cations were not subjected to similar detailed studies, although some isomers were examined by quantum-chemical methods. The heats of formation of the CH 3 CF 2 + , CH 2 FCHF + , and CHF 2 CH 2 + cations were calculated at the SCF level . Brum et al .…”
Section: Introductionmentioning
confidence: 99%